Three dimension printing and Masquelet's induced membrane technique in mandibular segmental defect reconstruction: A case report - XIAO Chenliang; SUN Lijun; HE Xiaoqing; XU Lu; ZHAO Xuda (Kouqiang hemian waike zazhi)
[Objective:] To report a case of ameloblastoma of mandible in our hospital using Masquelet's induced membrane technique (MIMT) to reconstruct mandibular segment defect in February 2021. [Methods:] According to the principle of MIMT, partial resection and implantation of bone cement were given in the first stage; with the help of digital surgery, three dimension printing model and pre-fabricated titanium mesh were used to transplant the iliac bone in the second stage; the plate and titanium mesh were removed in the third stage. [Results:] According to the post-operation CT images and intraoperative findings, the bone regeneration shows a good result with MIMT. [Conclusion:] MIMT can be further studied in the reconstruction of mandibular segmental defect.